Agave dealbata E.Morren ex K.Koch (Asparagaceae), the correct name for Agave dasylirioides Jacobi & C.D.Bouché (Nomenclature of Agave L. I) - Thiede, Joachim (Phytotaxa, 2014)
The genus Agave Linné (1753: 323; Asparagaceae-Agavoideae) has played an important role for the indigenous civilizations of North America (“man-Agave symbiosis”) and is of considerable economical and horticultural importance (Gentry 1982). Many new Agave species were introduced between about 1860 and 1890 particularly from Mexico. Frequently, new taxa have a complicated nomenclatural history with often multiple introductions or descriptions by different, partly competing authors and in publications often difficult to access (e.g., Govaerts & Thiede 2013). This has led to a considerable number of incorrect author citations and/or places of publication in taxonomic treatments as well as databases such as IPNI (2013). In the framework of a second, updated edition of a taxonomic synopsis of Agave (Thiede, in prep.), at least some uncertain and controversial nomenclatural issues will need to be addressed, starting here with A. dealbata.